2019
DOI: 10.1007/s13213-019-01487-2
|View full text |Cite|
|
Sign up to set email alerts
|

Phylogenetics and antibacterial properties of exopolysaccharides from marine bacteria isolated from Mauritius seawater

Abstract: Purpose The marine environment harbours diverse bacterial species which can be exploited for the production of valuable compounds such as exopolysaccharides (EPS) which hold promises for biotechnological applications. The coastal waters of Mauritius is a relatively underexplored marine environment and in this study, isolated bacterial species were tested for the production of EPS exhibiting antibacterial properties against human bacterial pathogens from the genera Acinetobacter, Bacillus, Campylobacter, Entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 95 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Importantly, glucose, ribose, fructose, and xylose sugars are commonly found in various bacterial EPSs along with a few other monosaccharides [ 9 ]. For instance, the EPS produced by Halomonas venusta and Alcaligenes faecalis isolated from the seawater of Mauritius consists of mainly fructose and glucose sugars [ 52 ]. The EPS from Bacillus licheniformis T14 consists of fructose, fucose, and glucose as major monosaccharides [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, glucose, ribose, fructose, and xylose sugars are commonly found in various bacterial EPSs along with a few other monosaccharides [ 9 ]. For instance, the EPS produced by Halomonas venusta and Alcaligenes faecalis isolated from the seawater of Mauritius consists of mainly fructose and glucose sugars [ 52 ]. The EPS from Bacillus licheniformis T14 consists of fructose, fucose, and glucose as major monosaccharides [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Low yields in nature are because EPS production requires 70% of cellular energy, e.g., in some cases, such as with Halomonas alkaliantarctica [81][82][83]. The production of EPSs is in competition with the formation of cell membrane components due to the metabolic pathways used to produce both compounds and their raw materials [74,84].…”
Section: Exopolysaccharidesmentioning
confidence: 99%
“…Within the medical field, EPSs have been used for treatments against arthritis [77], obesity, and colitis [72], as antivirals, antibacterials [84], and antioxidants, and some against certain types of cancer such as breast cancer, where it has been shown that they increase apoptosis in cancer cells [89].…”
Section: Exopolysaccharidesmentioning
confidence: 99%
“…Raffinose carbohydrate was significantly present in the HPLC analysis for the aforementioned EPS with a significant peak at a retention time of 3.910. Halophilic species such as Bacillus, Halomonas, Psychrobacter, and Alcaligenes produced eight EPS compounds with antimicrobial efficacies, and E15 strains were reported to be more active against B. cereus, S. aureus, S. saprophyticus, Enterobacter cloacae, Proteus mirabilis, MRSA, Enterococcus faecalis, Streptococcus pneumonia, Acinetobacter sp, and Campylobacter jejuni with MICs ranging between 250 and 500 µg/mL [120]. E37 also exhibited a wide antimicrobial activity with 250, 62.5, 125, and 500 µg/mL MICs, respectively, against the same pathogens mentioned above.…”
Section: Exopolysaccharidesmentioning
confidence: 99%